Urban expansion and environmental impacts: an analysis of urban intervention projects for the city of Teresina, Piauí - Melo Filho, José Maria Marques de (Geosaberes, 2018)
The present work seeks to discuss how the production of urban space influences the socio-spatial dynamics, considering projects of intervention in the city of Teresina, considering the relation of its implications for society and impact on the environment. After the theoretical characterization of social agents, the study emphasized the importance of urban planning and management, highlighting the complementary character that each has within the city organization, combining this analysis with the concerns regarding the impacts caused to the natural environment. The interest in this theme started from the observation that the city of Teresina presents an expressive expansion, but with respect to the urban interventions in the road that follow its frank transformation, they are slow in their execution and often there is no study on the implications That can cause in the social dynamics and the natural environment of the city. For the accomplishment of this work it was used as methodology of search systematized search in the scientific databases of Capes Newspapers, Scielo and Web of Science, besides documentary analysis of official records on the city of Teresina. Through what was researched it was noticed that the implantation of urban interventions has been carried out without there being in many cases a concern with the environmental issue, and the planning and management measures present failures in the execution of their actions. From this work it is hoped to contribute to the need for effective changes in the management and planning forms aimed at intervening in the urban, without generating great damages to the environment.